Menstrual restriction and perceived stress among adolescent grls of lower secondary school in Kailali district, Nepal. - Dahal,Alisha (2019)
ABSTRACT: Fueled by ignorance and myth, menstrual restriction has had its root in Nepalese society since eras. With various Hindu mythologies, it is forced upon women so as they are unable to perform daily works as usual with such restrictions. The more severe form of restriction such as Chaupadi has killed many women and young child due to suffocation, snakebite, rape and other serious forms. Although it has been criminalized by the law no visible impact of the law has been seen yet. Excluding the hormonal imbalance and physical pain that women go through during such discriminatory practice, such hazardous practices also affect the mental health of the young girls which haven't been yet explored so for this reason this study is very important for the physical, social and psychological wellbeing of the adolescent girls and the community. The aim of this study is to access the prevalence and perceived stress due to menstrual restriction among Adolescent girls of Lower secondary school in Kailali District, Nepal. The study carried out, was a descriptive, cross-sectional study conducted among 370 respondents, where proportionate random sampling technique was used to recruit study respondents. The study was conducted at the secondary school of Godawari Municipality, Kailali, Nepal. Pretesting of the questionnaire was done among 10% of the population in Kathmandu with a structured questionnaire and a Likert scale. Among different ethnic groups present perceived stress was found to be comparatively high among Upper caste groups and Dalits since they religiously follow menstrual restriction in contrast to disadvantaged Janajati of hills. In addition, larger the household sizes the level of perceived stress was moderately high among them. Menstrual restriction and perceived stress were measured about each type of menstrual restriction showing significant association between more that 80% of the different measured level of restrictions studied. Menstrual Restriction related practices such as Restricted to enter inside house, Sent to Chau-Goth, Restricted to touch male members, Restricted to touch livestock or animals, Restricted to eat together with family, Restricted to consume dairy products, Restricted to participate in cultural rituals, Restricted to sleep in any bed, Restricted and restricted to use heavy blankets and mattresses were associated with Perceived stress. Keeping this situation in mind, further researches should be conducted among the adolescent girls to measure the level of Perceived stress in the population.